2014
DOI: 10.1002/wrna.1268
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the potential of hepatitis C virus internal ribosome entry site domains to modulate translation initiation via their structure and function

Abstract: Translation initiation in the hepatitis C virus (HCV) occurs through a cap-independent mechanism that involves an internal ribosome entry site (IRES) capable of interacting with and utilizing the eukaryotic translational machinery. In this review, we focus on the structural configuration of the different HCV IRES domains and the impact of IRES primary sequence variations on secondary structure conservation and function. In some cases, multiple mutations, even those scattered across different domains, led to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 100 publications
(315 reference statements)
0
41
0
Order By: Relevance
“…The IRES also binds directly to eIF3 (Sizova et al, 1998), which along with the eIF2-containing TC have been described as capable of progressing the HCV IRES preinitiation complex (PIC) to an elongation-competent 80S ribosome (Pestova et al, 1998b). These and other studies have pointed to a mechanism in which a naked (unbound by factors) 40S subunit first binds directly to the IRES RNA through interactions with dIII (Ji et al, 2004; Otto and Puglisi, 2004), placing the start codon into the P site of the decoding groove, followed by recruitment of eIF3 by IRES subdomain IIIb (dIIIb) and association of the TC to position Met-tRNA i Met to form a 48S* complex (asterisk denotes noncanonical assembly and composition) (reviewed in: [Fraser and Doudna, 2007; Khawaja et al, 2015]). Although biochemical data suggest a step-wise recruitment of essential translation components, it has also been suggested that the first step in HCV IRES-driven translation could be binding to an assembled 43S PIC (40S pre-bound by other factors) (Berry et al, 2010; Hellen, 2009; Jackson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IRES also binds directly to eIF3 (Sizova et al, 1998), which along with the eIF2-containing TC have been described as capable of progressing the HCV IRES preinitiation complex (PIC) to an elongation-competent 80S ribosome (Pestova et al, 1998b). These and other studies have pointed to a mechanism in which a naked (unbound by factors) 40S subunit first binds directly to the IRES RNA through interactions with dIII (Ji et al, 2004; Otto and Puglisi, 2004), placing the start codon into the P site of the decoding groove, followed by recruitment of eIF3 by IRES subdomain IIIb (dIIIb) and association of the TC to position Met-tRNA i Met to form a 48S* complex (asterisk denotes noncanonical assembly and composition) (reviewed in: [Fraser and Doudna, 2007; Khawaja et al, 2015]). Although biochemical data suggest a step-wise recruitment of essential translation components, it has also been suggested that the first step in HCV IRES-driven translation could be binding to an assembled 43S PIC (40S pre-bound by other factors) (Berry et al, 2010; Hellen, 2009; Jackson et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In both models, it is proposed that subsequent GTP hydrolysis by eIF2, directed by eIF5 and enhanced by IRES dII, induces factor release and subunit joining (Locker et al, 2007). Mutations to different parts of the HCV IRES inhibit specific steps in the pathway (Berry et al, 2010; Filbin and Kieft, 2011; Kieft et al, 2001; Sizova et al, 1998; Spahn et al, 2001) (reviewed in: [Khawaja et al, 2015; Lukavsky, 2009]), which is proposed to be similar in other type 3 IRESs (Kolupaeva et al, 2000; Pestova et al, 1998b; de Breyne et al, 2008). In addition, the HCV IRES can also initiate translation when eIF2 is inhibited by phosphorylation of its alpha subunit (Koev et al, 2002; Robert et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to cardioviruses, HCV RNA expression is driven by IRES-mediated translation initiation [77]. Under cellular stress conditions, specific domains of HCV IRES interact with the small ribosomal subunit and the initiation factors eIF3 and eIF5B (Figure 1, left), allowing expression of viral RNA [79]. In addition, some viruses from other families unrelated to cardioviruses are known to target cells of the cardiovascular system and contribute to the etiology and progression of CVDs (for a detailed review, see [80]).…”
Section: Iressmentioning
confidence: 99%
“…The HCV 5′UTR contains four domains (I–IV) (Figure ). Whereas domains I and II are involved in viral replication, the IRES spans domains II and III and domain IV is present in HCV but absent in HCV‐like viruses . Interestingly, domain I contains two binding sites for a liver‐specific microRNA miR‐122 which activates HCV replication .…”
Section: Viral Ires Classificationmentioning
confidence: 99%